Effect of Different Early-Season Sprays on Blossom Blight Incidence and Yield in Peach Orchards, San Pedro, Argentina - Mitidieri, Mariel Silvina (2006)
Blossom blight and fruit brown rot, caused by Monilinia laxa and M. fructicola cause high crop loss on peach orchards, in Buenos Aires province, Argentina. Early season sprays are recommended to reduce blossom and twig blight incidence. Carbendazim resistant Monilinia strains were found in several San Pedro peach orchards. The other systemic fungicides registered, at the moment, belong all to the demethylation inhibiting (DMI) family. Tebuconazole, a DMI fungicide, provides very good control for fruit brown rot. The objective of this work was to determine if tebuconazole applications on bloom provide a better control of Monilinia spp. compared with a broad spectrum fungicide spray. Treatments consisted of 1) Control, 2) Captan (WP 80%, 250 g/100 L) and 3) Tebuconazole (EC 43%, 30 mL/100 L), applied at 40-50% and 90-100% bloom. During 2001/02 more fruits per plant (P>0.05) and a lower incidence of fruit brown rot after harvest were obtained with tebuconazole treated plots. During 2002/03, lower bloom blight incidence (P>0.01) and more fruits per plant were obtained with tebuconazole treated plots. During 2003/04 more fruits per plant and significantly higher yields per plant (P>0.05) were obtained after applications with tebuconazole.